The influence of capital structure, liquidity, and operational cost efficiency on firm value with profitability as an intervening variable in banking companies listed on the Indonesia Stock Exchange for the period 2019–2023 - Ajis Muslim; Subur Karyatun (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2025)
Capital structure, liquidity, and operating cost efficiency are important factors that influence company performance, especially banking companies. This study aims to analyze the effect of capital structure, liquidity, and operating cost efficiency on profitability and firm value. This study uses the regression analysis method to test the proposed hypothesis. The data also used is data from banking companies listed on the indonesia stock exchange during the 2019-2023 period. Hypothesis testing is carried out using linear regression tests to analyze the relationship between variables. The findings prove that capital structure has a significant positive effect on profitability, but has no direct effect on firm value. Liquidity has no significant effect on profitability, but has a negative effect on firm value. Operating cost efficiency is proven to have a significant positive effect on profitability, and firm value through profitability.